A comparative study of the effect of the Time for Dementia programme on medical students. (28th March 2021) - Banerjee, Sube; Jones, Christopher; Wright, Juliet; Grosvenor, Wendy; Hebditch, Molly; Hughes, Leila; Feeney, Yvonne; Farina, Nicolas; Mackrell, Sophie; Nilforooshan, Ramin; Fox, Chris; Bremner, Stephen; et al.
ABSTRACT: Background: Traditional healthcare education typically focuses on short block clinical placements based on acute care, investigations and technical aspects of diagnosis and treatment. It may therefore fail to build the understanding, compassion and person‐centred empathy needed to help those with long‐term conditions, like dementia. Time for Dementia was developed to address this. Method: Parallel group comparison of two cohorts of UK medical students from universities, one participating in Time for Dementia (intervention group) and one not (control group). In Time for Dementia students visit a person with dementia and their family in pairs for 2 hours three times a year for 2 years, the control group received their normal curriculum. Results: In an adjusted multilevel model (intervention group n = 274, control n = 112), there was strong evidence supporting improvements for Time for Dementia participants in: total Approaches to Dementia Questionnaire score (coefficient: 2.19, p = 0.003) and its person‐centredness subscale (1.32, p = 0.006) and weaker evidence in its hopefulness subscale (0.78, p = 0.070). There was also strong evidence of improvement in the Dementia Knowledge Questionnaire (1.63, p < 0.001) and Dementia Attitudes Scale (total score: 6.55, p < 0.001; social comfort subscale: 4.15, p < 0.001; dementia knowledge subscale: 3.38, p = 0.001) scores. No differences were observed on the Alzheimer's Disease Knowledge Scale, the Medical Condition Regard Scale or the Jefferson Scale of Empathy. Discussion: Time for Dementia may help improve the attitudes of medical students towards dementia promoting a person‐centred approach and increasing social comfort. Such patient‐focused programmes may be a useful complement to traditional medical education. Key points: Traditional healthcare education with its acute care focus may fail to build the understanding, compassion and person‐centred empathy needed to help those with long‐term conditions, such as dementia. We conducted a scoping review of enhanced placements in dementia for healthcare students searching PubMed, SCOPUS and PsycINFO and grey literature. We found a small number of programmes, with positive, but not definitive, data on their value. They were often elective parts of curricula, so relatively few students participated. Data on comparative effectiveness were sparse. This evaluation provides proof of concept evidence that the Time for Dementia programme where students visit a person with dementia and their family in pairs for 2 hours every term for 2 years, can be made a core part of the curriculum at medical schools; the people with dementia and their carers visited are the teachers/mentors in this relationship. These data provide positive evidence of the value of introducing a longitudinal experience of dementia as a part of the core curriculum for medical students. Students improved in terms of their attitudes towards dementia, becoming more person‐centred and having greater social comfort with, and hopefulness for, those with dementia. Research is needed in larger representative groups and comparative studies with other educational approaches. Its effectiveness in other healthcare student groups warrants study. This longitudinal approach might be of value in building positive attitudes and understanding for other marginalised patient groups.